Diseño e implementación de nueve procedimientos técnicos como parte del Sistema de Gestión de Calidad del LabCIVCO - Segura-Fernández, María (Instituto Tecnológico de Costa Rica, 2010)
This document was developed as part of the Quality Management System of LabCIVCO, with the objective of designing and implementing technical procedures for nine tests in the area of aggregates, for each one were prepared an instructional and technical records (physical and digital) based on the international specifications of AASHTO and ASTM respective compliance with the requirements set forth by the Costa Rican Accreditation Entity, due to LabCIVCO want to accredit these tests in the near future. A diagnosis of existing equipment required in each test was made and was evaluated the performance of laboratory staff in the execution of three of them: Loose and Compacted Unit Weight of Coarse Aggregate (AASHTO T-19, ASTM C-29), Specific Gravity and Absorption Coarse and Fine Aggregate (AASHTO T-84, ASTM C-127 and AASHTO T-85, ASTM C-128), and Resistance to Degradation by Abrasion (AASHTO T-96, ASTM C-131). The evaluation was made based on the obtained results of performance tests and the used procedures. The results indicate the need for standardized procedures through regular training and performance tests in order to ensure the reliability of the results to the general public.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Agregados; Ensayo; Prueba; Desempeño; Calidad